2015
DOI: 10.1136/bmjopen-2015-008046
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the CHEST Australia Trial: a phase II randomised controlled trial of an intervention to reduce time-to-consult with symptoms of lung cancer

Abstract: IntroductionLung cancer is the most common cancer worldwide, with 1.3 million new cases diagnosed every year. It has one of the lowest survival outcomes of any cancer because over two-thirds of patients are diagnosed when curative treatment is not possible. International research has focused on screening and community interventions to promote earlier presentation to a healthcare provider to improve early lung cancer detection. This paper describes the protocol for a phase II, multisite, randomised controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Our study provides insights into how to intervene at different levels of influence to improve the likelihood of patients and health care professionals suspecting and acting on potential lung cancer. Studies testing health care–based interventions addressing symptom awareness/normalisation and fatalism in patients at high risk of lung cancer are ongoing . Our study highlights the potential need for similar interventions in patients with COPD, and we have developed recommendations in order to help mitigate specific issues within this sample (see Box ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study provides insights into how to intervene at different levels of influence to improve the likelihood of patients and health care professionals suspecting and acting on potential lung cancer. Studies testing health care–based interventions addressing symptom awareness/normalisation and fatalism in patients at high risk of lung cancer are ongoing . Our study highlights the potential need for similar interventions in patients with COPD, and we have developed recommendations in order to help mitigate specific issues within this sample (see Box ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies testing health care-based interventions addressing symptom awareness/normalisation and fatalism in patients at high risk of lung cancer are ongoing. 27,28 Our study highlights the potential need for similar interventions in patients with COPD, and we have developed recommendations in order to help mitigate specific issues within this sample (see Box 1). For example, raising the awareness of the link between cancer and COPD in patients will help in identifying symptoms as something different, but this needs to be dealt with sensitively to avoid increased fatalism.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also indicated the potential effectiveness of targeted, local GP-based interventions, which combine symptom awareness, education, and strategies that reduce complexity in appointment scheduling specifically for patients at-risk of lung cancer[34,45,46]. A randomised controlled trial of one such intervention is currently underway in Australia[47]. …”
Section: Discussionmentioning
confidence: 99%
“…promoting earlier presentation of potential cancer symptoms [3][4][5][6][7] ; the use of new technologies in the assessment of pigmented skin lesions 8 ; the use of computerized decision-support tools in the diagnosis of cancer in primary care 9 ; cancer-specific education for general practitioners (GPs) 5,10 ; direct access to low-dose CT for the early detection of lung cancer in primary care 11 ; and lower symptom thresholds for urgent use of chest radiography 12 . Thus far, no trial has included a sufficiently large cohort to address the issue of whether or not expedited cancer diagnosis in primary care is beneficial, in terms of either mortality or morbidity.…”
Section: [H1] Benefits Of Expedited Symptomatic Diagnosis [H2] Types mentioning
confidence: 99%